Efek Pemaparan Komposit High Density Polyethylene (HDPE) Limbah Berpenguat Serat Cantula Agave Terhadap Perubahan Sifat Lentur dan Impak - Siswanto; Teguh Wiyono (Politeknosains, 2020)
Research on composite material title: Effects of High Density Polyethylene (HDPE) Composite Agave Fiber Reinforced Waste on Changing Flexural and Impact Properties, this aims to determine the effect of exposure to changes in mechanical properties of composites. Composites were tested for the flexural and impact properties, in order to determine the surface morphology of the composite fracture, SEM photographs were taken. The composite matrix uses HDPE polymer waste bottles, waste plastic materials are cleaned and ground and sieved into 40-60 mesh. Composite reinforcement uses cantula fibers which are cut into 10 mm lengths. Composites are made by printing using hot press machines, pressing machines 30 bar, temperature 115 0C for 10 minutes, making composites with 40% fiber volume fraction. After the composite is formed, it is cut into pieces based on flexural test specimens using the ASTM D 6272 standard (127 x 12.7 x 3.2 mm) and ASTM D 5941 (80 x 10 x 4.0 mm) impact test specimens. The specimen is then exposed in an open location so that the specimen is exposed to all environmental effects such as sun exposure, rain and wind. The variation of time duration of exposure is 0, 30, 60, and 90 days with an exposure angle of 50. To find out the surface morphology of the broken specimen, SEM photographs were taken. The results of testing on the composite data obtained that the composite without exposure has a flexural strength of 45.93 N / mm2 and an impact strength of 43.13 Kj / m2. After being exposed to composites, the mechanical properties decreased, the lowest flexural strength decreased at 30 days exposure (2.96% reduction), the greatest decrease in flexural strength occurred at 90 days (decreased 5.39%). The decrease in impact strength due to the lowest exposure occurred at 30 days exposure (decrease of 17.41%), the greatest decrease in impact strength occurred at 90 days exposure (decrease of 64.02%).